2016
DOI: 10.1097/inf.0000000000001320
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of Unboosted Atazanavir in Treatment-experienced HIV-infected Children, Adolescents and Young Adults

Abstract: HIV protease inhibitor use in pediatrics is challenging due to the poor palatability and/or toxicity of concomitant low-dose ritonavir. Atazanavir without ritonavir (unboosted) is not recommended for patients with prior virologic failure; a common problem for perinatally-infected adolescents. Atazanavir 400 mg once-daily provided suboptimal exposure. Higher unboosted doses or splitting the daily dose to twice-daily warrants investigation in this treatment-experienced population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…69 Bunupuradah et al 67 showed that 200-mg ATV boosted with 100 mg of ritonavir within a regimen containing TDF was able to achieve ATV levels comparable with adult levels in Asian children aged 6–18 years. Another study, by Cressey et al, 70 investigated the possibility of using unboosted ATV in ART-experienced Thai children unable to take ritonavir. Doses of 400-mg and 600-mg unboosted ATV did not achieve target C trough levels and were highly variable between patients.…”
Section: Methodsmentioning
confidence: 99%
“…69 Bunupuradah et al 67 showed that 200-mg ATV boosted with 100 mg of ritonavir within a regimen containing TDF was able to achieve ATV levels comparable with adult levels in Asian children aged 6–18 years. Another study, by Cressey et al, 70 investigated the possibility of using unboosted ATV in ART-experienced Thai children unable to take ritonavir. Doses of 400-mg and 600-mg unboosted ATV did not achieve target C trough levels and were highly variable between patients.…”
Section: Methodsmentioning
confidence: 99%
“…The maximum concentration (Cmax) is the highest concentration of a drug in the blood, cerebrospinal fluid, or target organ after a dose is given. The Cmax of ATV in plasma after a standard dose ranges from 1.5 to 8 µM in patients [20][21][22]. 4 x 10 4 /ml cells (total volume of 30 ml) were cultured with different concentrations of ATV, multiplicities of Cmax-0, 2.5, 5.0, 7.5, 15, 22.5, and 30.0 µM.…”
Section: Cell Culture and Drugsmentioning
confidence: 99%